Physical and Chemical Properties of Dental Restorative Materials That Affect Their Clinical Efficiency. - Drakul, Dejan (Foundations of materials science and engineering, 2020)
The work at hand deals with restorative dental materials that are being used for the treatment of the most common dental disease - dental caries (but for treatment of cuneiform erosions as well). The materials this work talks about are dental amalgams (metallic dental restorative material), dental resin composites, and glass-ionomer cements. This work looks at these materials from the perspective of their physical and chemical properties that influence the clinical efficiency of these materials (the quality of restorations). Dental amalgams, dental resin composites, glass-ionomer cements, physical and chemical properties, clinical efficiency of dental restorative materials Bioscience and Medicine.